SEKURITISASI TERHADAP IMIGRAN NEGARA MAYORITAS MUSLIM DI AMERIKA SERIKAT ERA PRESIDEN DONALD TRUMP - Adi Joko Purwanto (SPEKTRUM, 2021)
This article will explain Donald Trump's securitization process regarding the issue of immigrants which has been the main agenda of his campaign since he ran for US president. Trump as a securitizing actor, America as an object of security issues and Trump used the idea of ​​security issues through the speech act. The Speech act regarding the issue of immigrants began at the beginning of his campaign until he elected as president of America. The Speech act was reiterated after Trump's hundred-day work at the White House and was implemented as a new migration policy, namely the banning of immigrants from 7 Muslim-majority countries where terrorism was inherent in Muslim society, especially after the 9/11 tragedy. The use of data in this paper uses internet-based methods. Keywords: Securitization, Securitizing Actor, object of security issues, Speech act, muslim immigrants